Synthesis of microporous carbon nanofibers with high specific surface using tetraethyl orthosilicate template for supercapacitors. (15th June 2016) - Sheng, Jie; Ma, Chang; Ma, Yuan; Zhang, Haixia; Wang, Ranran; Xie, Zhenyu; Shi, Jingli
Abstract: Microporous carbon nanofibers (CNFs) with a high specific surface area were prepared by sol–gel, electrospun, carbonization and pickling processes. Resol type phenolic resin (PF) acted as carbon source, tetraethyl orthosilicate (TEOS) worked as template and polyvinyl-pyrrolidone worked as spinning additives. The specific surface area and total pore volume of the CNFs were increased obviously with the increased amount of TEOS. A high specific area of 2164 m 2 g −1, high microporosity and relatively narrow pore size distribution were achieved. The electrochemical performance was evaluated in 6 M KOH aqueous solution. The microporous CNFs exhibited outstanding electrochemical performance as binder-free electrode of supercapacitors, including a high specific capacitance (316 F g −1 at 0.2 A g −1 ), considerable rate performance (210 F g −1 at 20 A g −1 ) and good cycle stability (95% after cycling 1000 times). The microporous CNFs were promising electrode materials for high-performanced supercapacitors. Highlights: Electrospun carbon nanofibers are obtained with phenolic resin as precursor and TEOS as template. Carbon nanofibers have high microporosity of 88% and surface area of 2164 m 2 g −1 . The high-surface-area carbon nanofibers can be directly made into electrode free of binder. A high capacitance of 316 F g −1 and good cycling stability are achieved.